Piano Braille Aksara Jawa: Media Pelestarian bagi Siswa Tunanetra SLBN Semarang Jawa Tengah - Ghurrotul Bariroh; Faiq Wahyu Nugraha; Amelia Nur Alifah; Eka Widiyanti; Eko Retno Mulyaningrum (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Semarang State Special Education School was one of the schools under the auspices of the government that provided education for children with special need from Pre-primary School to Senior High School. Blind was one of the persons with disabilities who were educated at Semarang State Special Education School. The introduction of culture in Indonesia was one of the education services taught at the Semarang State Senior High Special Education School. However, the difficulty of taught braille to blind students was a factor in the not being taught Javanese script to blind students. Through the Javanese script braille piano helps Semarang State Senior High Special Education School in introducing Javanese script to blind students. In its implementation was socialization then proceed with training and mentoring activities in provided more understanding and avoiding misconceptions in learned Javanese characters in blind students. The successful implementation of community service programs refers to the indicators of the accuracy of reading and writing Braille Javanese characters for blind students. Through this program, in addition to being able to read and wrote Javanese script, blind students play a role in preserving Javanese script as one of Indonesian culture.